PENINGKATAN PRODUKTIVITAS PABRIK KERTAS DENGAN MEMPERTIMBANGKAN POWER FAKTOR DAN MENGGUNAKAN KAPASITOR BANK DI PT DAYASA ARIA PRIMA - Rezza Agung Fahlevi; Prihono (JURNAL REKAYASA SISTEM INDUSTRI, 2023)
This study aims to determine the increase in paper mill productivity with the ETAP 12.6 simulation method. The progress of the company as a business organization has increased activity, increased performance and increased productivity in the electrical system at PT Dayasa Aria Prima to take strategic steps in minimizing expenditure costs on the electrical system and developing an electrical system based on ETAP 12.6 analysis and simulation at PT Dayasa Aria Prima. Changes in the value of the power factor will have an impact on decreasing the value of cos φ. Based on the analysis and simulation of ETAP 12.6 it is known that the power factor of PT. Dayasa Aria Prima is around 0.70% where the company has to pay a fine to PLN. To eliminate or eliminate fines, an increase is made to meet the standard requirements for power factor which must be more than 0.85%. Installing a capacitor bank with a power factor is an effective and efficient way to increase productivity so that companies can control and measure the productivity and cost efficiency of the company